Genetic Features of HIV-1 Integrase Sub-Subtype A6 Predominant in Russia and Predicted Susceptibility to INSTIs - Alina Kirichenko; Ilya Lapovok; Pavel Baryshev; David A. M. C. van de Vijver; Jeroen J. A. van Kampen; Charles A. B. Boucher; Dimitrios Paraskevis; Dmitry Kireev (Viruses, 2020)
The increasing use of the integrase strand transfer inhibitor (INSTI) class for the treatment of HIV-infection has pointed to the importance of analyzing the features of HIV-1 subtypes for an improved understanding of viral genetic variability in the occurrence of drug resistance (DR). In this study, we have described the prevalence of INSTI DR in a Russian cohort and the genetic features of HIV-1 integrase sub-subtype A6. We included 408 HIV infected patients who were not exposed to INSTI. Drug resistance mutations (DRMs) were detected among 1.3% of ART-naïve patients and among 2.7% of INSTI-naïve patients. The prevalence of 12 polymorphic mutations was significantly different between sub-subtypes A6 and A1. Analysis of the genetic barriers determined two positions in which subtype A (A1 and A6) showed a higher genetic barrier (G140C and V151I) compared with subtype B, and one position in which subtypes A1 and B displayed a higher genetic barrier (L74M and L74I) than sub-subtype A6. Additionally, we confirmed that the L74I mutation was selected at the early stage of the epidemic and subsequently spread as a founder effect in Russia. Our data have added to the overall understanding of the genetic features of sub-subtype A6 in the context of drug resistance.